2019
DOI: 10.1007/s00535-019-01581-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol 3350 plus electrolytes for chronic constipation: a 2-week, randomized, double-blind, placebo-controlled study with a 52-week open-label extension

Abstract: Background Although polyethylene glycol 3350 plus electrolytes (PEG3350 + E) is the most widely used osmotic laxative in Europe, prospective data on its long-term (over 6 months) safety and efficacy are not available to date. Methods Japanese patients with chronic constipation were randomized to receive PEG3350 + E or placebo for 2 weeks orally. Following this, the patients received PEG3350 + E in the 52-week extension study. The starting dose was 13.7 g/day dissolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Regarding stool consistency, in the previous study, the rates of improvement in stool consistency (BSFS 3, 4, and 5) at the first and second weeks were 87.3% and 80.0%, respectively, which was comparable to that in our study (90.6%) [ 18 ]. The authors analyzed the rates of complete SBMs, defined as SBMs with a feeling of complete evacuation, and the rates in the first and second weeks were 23.8% and 37.5%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding stool consistency, in the previous study, the rates of improvement in stool consistency (BSFS 3, 4, and 5) at the first and second weeks were 87.3% and 80.0%, respectively, which was comparable to that in our study (90.6%) [ 18 ]. The authors analyzed the rates of complete SBMs, defined as SBMs with a feeling of complete evacuation, and the rates in the first and second weeks were 23.8% and 37.5%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The number of SBMs/week in the PEG group taking PEG for 4 weeks was 4.40 ± 2.58 compared to 3.11 ± 1.93 in the placebo group ( p < 0.00001) [ 17 ]. A recent Japanese RCT using the same dose of PEG3350+E as our study involved 80 patients taking PEG+E, with a mean age of 44.3 ± 11.6 years old and 88.8% females [ 18 ]. The baseline number of SBMs/week was 1.6 ± 0.9, which increased during the first and second week of PEG3350+E prescription to 3.36 (95% confidence interval (CI): 2.81-3.92) and 4.27 (95% CI: 3.36-4.92), respectively, with responder rates of 80.0% and 86.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that PEG3350+E significantly resolved constipation compared with placebo in the 2-week, randomized, double-blinded confirmatory phase of a PEG3350+E study, and the efficacy of PEG3350+E lasted for the entire 52-week extension phase, with good tolerability in Japanese adults with chronic constipation. 29…”
Section: Discussionmentioning
confidence: 99%
“…Anorectal biofeedback, transformational infection, nerve stimulation, colonial surgery and other treatments have brought significant economic burdens and thus considerable healthcare utilization to patients. [ 8 – 10 ] At the same time, FC seriously impairs the physical and mental health of patients and affects their quality of life [ 11 ] . Therefore, many people, including those who do not improve with existing medications or suffer many side effects, are interested in complementary and alternative medicine.…”
Section: Introductionmentioning
confidence: 99%